Chronobiological Approaches to Alzheimer's Disease - M. Stranahan, Alexis (Current Alzheimer Research, 2012)
Dynamic circadian rhythms contribute to memory formation, and the hormonal and neurochemical changes that follow circadian patterns are frequently dysregulated with aging. The effect of aging on circadian rhythms is a doubleedged sword; on one hand, poor sleep quality compromises neuronal structure and function in regions that support cognition, and on the other hand, perturbation of central and peripheral oscillators changes the hormonal milieu, with consequences for neuroplasticity. In the current review, recent developments surrounding the circadian regulation of memory formation are described, with reference to how mechanisms that support temporal coding might change with advancing age. The cognitive consequences of changes in sleep patterns are also discussed. New roles for the circadian clock genes period-1, period-2, and bmal1 in memory formation are discussed in the context of age-related cognitive decline. The potential for chronobiological approaches to the treatment and prevention of Alzheimer's disease merits further exploration from a pharmacotherapeutic perspective, as the timing of drug delivery could potentiate or diminish treatment efficacy.
Keywords: gene expression